Readiness of emergency obstetric and newborn care in public health facilities in Afghanistan between 2010 and 2016. Issue 3 (25th December 2019) - Ansari, Nasratullah; Tappis, Hannah; Manalai, Partamin; Anwari, Zelaikha; Kim, Young Mi; van Roosmalen, Jos J.M.; Stekelenburg, Jelle
Abstract: Objective: To assess changes in readiness to provide emergency obstetric and newborn care (EmONC) in health facilities in Afghanistan between 2010 and 2016. Methods: A secondary analysis was performed of a subset of data from cross‐sectional health facility assessments conducted in December 2009 to February 2010 and May 2016 to January 2017. Interviews with health providers, facility inventory, and record review were conducted in both assessments. Descriptive statistics and χ 2 tests were used to compare readiness of EmONC at 59 public health facilities expected to provide comprehensive EmONC. Results: The proportion of facilities reporting provision of uterotonic drugs, anticonvulsants, parenteral antibiotics, newborn resuscitation, and cesarean delivery did not change significantly between 2010 and 2016. Provision of assisted vaginal deliveries increased from 78% in 2010 to 98% in 2016 ( P <0.001). Fewer health facilities had amoxicillin (61% in 2016 vs 90% in 2010; P <0.001) and gentamicin (74% in 2016 vs 95% in 2010; P <0.002). The number of facilities with at least one midwife on duty 24 hours a day/7 days a week significantly declined (88% in 2016 vs 98% in 2010; P =0.028). Conclusion: Despite a few positive changes, readiness of EmONC services in Afghanistan in 2016 had declined from 2010 levels. Abstract : Despite a number of positive changes, readiness of emergency obstetric and newborn care services declined between 2010 and 2016 in health facilities in Afghanistan.